FORMATION OF PROFESSIONAL COMPETENCE FUTURE FOREIGN LANGUAGE TEACHER AS PEDAGOGICAL PROBLEM (Pedagogy of Higher and Secondary Education, 2002)
The article deals with the problem of the formation of the professional competence of a future foreign language teacher. The essence of the notion of “professional competence of a future foreign language teacher ” and its structure has been revealed.Pedagogical conditions which are to be created to form the professional competence of a future foreign language teacher, have been determined.